Transition to Agricultural Market Economies: The Future of Kazakhstan, Russia and Ukraine 2015
DOI: 10.1079/9781780645353.0122
|View full text |Cite
|
Sign up to set email alerts
|

Does agroholding membership increase productivity and efficiency in Russian agriculture? Evidence from agroholdings in the Belgorod Oblast.

Abstract: There has been little research on the effects of group membership on the productivity and efficiency of agricultural enterprises in Russia. This chapter analyses whether farms in the Belgorod Oblast of Russia that belong to agroholdings (entities composed of groups of agricultural enterprises) perform better than do independent farms (individual agricultural enterprises that are independent of agroholdings). We calculate partial land and labour productivity, total factor productivity and technical efficiency s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similarly, agroholding members can access the machinery, equipment, etc., of the parental organization, ensuring higher quantities of available resources. Our findings confirm the results of Hahlbrock and Hockmann (2011), wherein farms that are members of agroholdings perform better in terms of production efficiency compared to nonmember farms in the Belgorod region of Russia. Furthermore, another study by Tleubayev et al (2021) observes a positive link between agroholding affiliation and financial performance among Russian agri-food enterprises.…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, agroholding members can access the machinery, equipment, etc., of the parental organization, ensuring higher quantities of available resources. Our findings confirm the results of Hahlbrock and Hockmann (2011), wherein farms that are members of agroholdings perform better in terms of production efficiency compared to nonmember farms in the Belgorod region of Russia. Furthermore, another study by Tleubayev et al (2021) observes a positive link between agroholding affiliation and financial performance among Russian agri-food enterprises.…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
“…These factors include the amount of farm subsidies paid by the government to farmers, access to supply chains, participation in insurance programs, and cooperative and agroholding membership. Several studies have investigated the development of technical efficiency in Russian agriculture during the transition years (Belyaeva and Hockmann, 2015;Bokusheva and Hockmann, 2006;Hahlbrock and Hockmann, 2011;Rada, Liefert, and Liefert, 2017;Sotnikov, 1998;Sedik, Trueblood, and Arnade, 1999;Voigt and Uvarovsky, 2001;Osborne and Trueblood, 2006); however, the relation between specific policy reforms and technical efficiency has not yet been assessed quantitatively before. We are especially not aware of any other study investigating the farm-level effects of subsidies in these two countries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of the agroholdings are vertically integrated, thereby having an access to raw commodities supply at lower transaction costs (Hermans et al, 2017). Indeed, an empirical study by Hahlbrock and Hockmann (2011) suggests that agroholding affiliated farms in Russia have higher adoption of new technologies and therefore are more efficient compared to independent farms. Moreover, Russian agroholdings operate in the most favorable regions in terms of both agro-climatic and logistics conditions (FAO, 2009;Rada et al, 2017), which gives them comparative advantages over stand-alone firms.…”
Section: Resultsmentioning
confidence: 99%
“…Existing literature on agroholdings is still immature, with empirical studies providing rather mixed results on the effects of agroholding affiliation on firm performance. Hahlbrock and Hockmann (2011) have studied the effects of agroholding membership on farm efficiency in the Belgorod region of Russia, and revealed that, on average, affiliated farms perform better in terms of efficiency compared to non-affiliated farms. On the other hand, a similar study by Hockmann et al (2005) revealed that agroholding members have lower economic efficiency compared to independent farms.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Regarding agroholdings' ongoing involvement in acquisitive activities, several studies have questioned the economic viability of this sort of growth (Balmann et al, 2013;Epstein et al, 2013;Hahlbrock and Hockmann, 2012;Hockmann et al, 2009). It is, however, worth noting that these studies focused mainly on general performance analyses with a few unique examples of the post-acquisition performance of farms.…”
Section: Introductionmentioning
confidence: 99%